PENINGKATAN AKURASI ARAH KIBLAT DALAM IBADAH MASYARAKAT CAMPUREJO KOTA KEDIRI - Risni, Titin Widya; Hendy, Hendy; Vitasmoro, Pramadya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2024)
The accuracy of the Qibla direction is a crucial requirement in performing prayers. However, errors in determining the Qibla direction are still common and can affect the validity of worship. To address this issue, a community service program was conducted at Musholla Al-Latief Campurejo, aiming to enhance the community's understanding and skills in accurately determining the Qibla direction. This program employed modern technological approaches and astronomical methods, designed participatively to actively involve the community. The methods included education, hands-on practice, and Qibla direction verification using the A'zam Kiblat technique and observations of the Rashdul Kiblat phenomenon. Tools such as digital applications like Qibla Finder and shadow observations of upright objects during the sun's alignment over the Kaaba were utilized. The program ran from July 11 to 20, 2024, involving collaboration between facilitators, mosque caretakers, and the local community. The results demonstrated an increased scientific understanding among participants regarding the importance of Qibla accuracy and their ability to verify the direction using modern technology. High community enthusiasm and synergy among stakeholders also strengthened solidarity and awareness of the significance of precision in prayer rituals. Thus, this program successfully provided practical solutions and made a tangible contribution to improving the quality of worship among the community. Keywords: Qibla direction; prayer worship (Sholat); astronomical methods; mosque management (takmir); modern technology.